ChemInform Abstract: Di‐ and Tri‐Cobalt Silicotungstates: Synthesis, Characterization, and Stability Studies. Issue 15 (25th March 2013) - Zhu, Guibo; Geletii, Yurii V.; Song, Jie; Zhao, Chongchao; Glass, Elliot N.; Basca, John; Hill, Craig L.
Abstract Compounds (IV), (V), and (VI) are characterized by single crystal XRD, cyclic voltammetry, IR, and UV/VIS spectroscopy.